PENGARUH FAKTOR SOSIAL DAN CITRA MEREK TERHADAP KEPUTUSAN MAHASISWA MEMILIH KULIAH DI FAKULTAS PERTANIAN UNIVERSITAS ISLAM SUMATERA UTARA MEDAN MELALUI SIKAP SEBAGAI VARIABEL INTERVENING - Nana Trisna Mei Br Kabeakan (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Decision to choose a university is generally made by most of the students who have completedtheir study at the Senior High Schools. The small number of state universities in Indonesia has providedan opportunity for private universities to be chosen by students who fail to enter state universities. One ofthe private universities in Medan is Universitas Islam Sumatera Utara (UISU) and one of the faculties inthis university is the Faculty of Agriculture. In the period of 2012-2015, there was the decrease in thenumber of new students at this faculty. Some factors which are assumed to influence students’ decision tochoose higher education are social factor, brand image, and attitude. The objective of the research wasto find out and to analyze the influence of social factor and brand image on students’ decision to choosethe Faculty of Agriculture UISU Medan with attitude as intervening variable. The research was anexplanatory research. The samples were 133 students, taken by using proportional random samplingtechnique. The data were analyzed by using path analysis with an SPSS software program. The result ofthe research showed that social factor had positive and significant influence on students’ attitude inchoosing the Faculty of Agriculture, UISU, Medan, it had positive and significant influence on students’decision to choose the Faculty of Agriculture, UISU, Medan, it indirectly had positive and significantinfluence on students’ decision to choose the Faculty of Agriculture, UISU, Medan, through attitude asintervening variable. Brand image had positive and significant influence on students’ attitude in choosingthe Faculty of Agriculture, it had positive and significant influence on students’ decision to choose theFaculty of Agriculture, UISU, Medan, it indirectly had positive and significant influence on students’decision to choose the Faculty of Agriculture, UISU, Medan, through attitude as intervening variable,and attitude had positive and significant influence on students’ decision to choose the Faculty ofAgriculture, UISU, Medan.